P-LME polymer nanocapsules stimulate naïve macrophages and protect them from oxidative damage during controlled drug release - Yamala A.K.; Nadella V.; Mastai Y.; Prakash H.; Paik P. (My University, 2025)
Using polymer-based nanocapsules as novel drug delivery systems have gained significant importance. In this work, we present poly-(N-Acryloyl L-Leucine methyl ester [pLME]) nanocapsules with hollow core (pLME) of size approximately ~160 nm (dia.) synthesized for the first time through the miniemulsion approach. Our study reveals that pLME are biocompatible and immune stimulatory in nature on macrophages, which are decisive for host immunity. These nanocapsules are effective for encapsulating and sustainable release of drug (SNP; nitric oxide donor) at a high extent ~1.04 μM mg-. pLME also demonstrated their potential of stimulating naïve macrophages toward the M1 phenotype for extended period of time indicating their adjuvant activity on immune system. Our data also demonstrated their antioxidant potential toward H2O2-induced oxidative stress in macrophages. These results suggest pLME as an effective drug/vaccine delivery material with immune adjuvant and cytoprotective efficacy warranting its pharmacological application. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48363. © 2019 Wiley Periodicals, Inc.